The Right Skills for the Job? Rethinking Training Policies for Workers - Almeida, Rita; Behrman, Jere; Robalino, David (Washington, DC: World Bank, 2013)
This book addresses the question of how to build and upgrade job relevant skills. Specifically, the authors focus on three types of training programs relevant for individuals who are leaving formal general schooling or are already in the labor market: pre-employment technical and vocational education and training (TVET); on-the-job training (OJT); and training-related active labor market programs (ALMPs). ALMPs are usually of shorter duration and target individuals who are seeking a second chance and who do not have access to TVET or OJT; these are often low-skilled unemployed or informal workers. Contrary to training-related ALMPs, pre-employment TVET is usually offered within the formal schooling track and tends to be administered by the ministries of education. The book discusses the main justifications for these programs and how they relate to market failures that can lead to underinvestment in training and misalignment between supply and demand for skills. Unfortunately, governments are also prone to failure and many of the programs that countries have adopted today are part of the problem and not the solution. This book proposes options to improve the design and implementation of current skills development systems. Clearly, the authors cannot cover all issues in detail. Training methods among TVET, OJT, and ALMP programs are quite different, ranging from classroom instruction, laboratory research, TVET workshops, and apprenticeship arrangements and internships in firms. All have different challenges and specificities. The report highlights the most important design features of the different programs and points to the main knowledge gaps and areas for future research and analysis. The book is organized into five chapters. Following this overview, chapter two introduces the policy framework that guides the analysis in the book. This framework describes the main market and government failures that require attention and identifies potential interventions to address them. Chapter's three to five then discuss the main challenges facing, respectively, TVET, OJT, and training-related ALMP programs and outlines recommendations to address them. The rest of this overview summarizes the main messages from each of the chapters and in the last section outlines the main knowledge gaps and proposes an agenda for future research and policy analysis.